(untitled) (Research, Society and Development, 2020)
Green banana flour has high production viability and high content of resistant starch, so it is widely used in the manufacture of cereal bars, bread and drinks. The variety of bananas used can influence the characteristics of the flour, requiring comparative studies on the cultivars. The objective was to elaborate and characterize green banana flours from the cultivars Pacovan, Prata and Willians, in terms of yield and chemical, physical-chemical and mineral composition. The moisture content, protein, ash, crude fiber, titratable acidity, pH, soluble solids, macro and micro minerals and the yield were determined. Flours cv Pacovan and cv Willians showed higher levels of minerals and cv Prata showed higher yield. The mineral content varies by species and the soil used. The yield varies with the moisture content. Flours produced from green bananas of the cultivars Pacovan, Prata and Willians can be used in dietary preparations, in order to enrich them nutritionally.